Scenario-Neutral Assessment of Rainfall–Erosion Sensitivity Using RUSLE in the Sempor Reservoir Catchment, Indonesia - Irfan Fadillah Widianto; Suroso; Purwanto Bekti Santoso (Journal of the Civil Engineering Forum, 2026)
Rainfall variability poses a substantial threat to reservoir sustainability in tropical monsoon catchments because changes in rainfall intensity and seasonality directly influence soil detachment, runoff generation, and sediment source pressure. Conventional climate–impact assessments commonly rely on a limited number of deterministic climate projections, which may obscure the broader sensitivity of catchment erosion to plausible rainfall changes. This study integrates a scenario–neutral (SN) framework with the Revised Universal Soil Loss Equation (RUSLE) to evaluate rainfall–erosion sensitivity in the Sempor Reservoir catchment, Central Java, Indonesia. Historical daily rainfall was used to establish the baseline, while systematic perturbations of annual precipitation, seasonal rainfall distribution, wet–day frequency, and extreme rainfall intensity were used to construct a broad rainfall–exposure space. Changes in rainfall erosivity were subsequently propagated through RUSLE while soil erodibility, topography, land cover, and support–practice factors were held constant. The resulting estimates represent potential hillslope soil loss and sediment–source pressure rather than direct measurements of sediment delivery or reservoir deposition. The results reveal pronounced seasonal and spatial contrasts. Wet–season rainfall contributes more than 60% of annual rainfall erosivity and approximately 70–80% of annual estimated soil loss. The greatest estimated erosion occurs where relatively high rainfall erosivity coincides with higher soil–erodibility, topographic, cover–management, and support practice factors. Increasing wet–season rainfall produces a marked increase in estimated soil loss, indicating that erosion sensitivity is influenced by rainfall timing and intensity as well as annual rainfall totals. The scenario neutral simulations reproduce baseline medians and seasonal patterns consistently but attenuate the upper distribution tails and consequently underrepresent rare extreme events. The integrated SN–RUSLE framework therefore provides a transparent approach for diagnosing rainfall–erosion sensitivity under climate uncertainty. The findings support prioritising wet–season erosion control, maintaining vegetation cover, and implementing spatially targeted conservation measures in areas with higher estimated erosion potential.